The interplay between financial conditions and monetary policy shocks - Marco Bassetto; Luca Benzoni; Trevor Serrao (Federal Reserve Bank of Chicago, 2016)
We study the interplay between monetary policy and financial conditions shocks. Such shocks have a significant and similar impact on the real economy, though with different degrees of persistence. The systematic fed funds rate response to a financial shock contributes to bringing the economy back towards trend, but a zero lower bound on policy rates can prevent this from happening, with a significant cost in terms of output and investment. In a retrospective analysis of the U.S. economy over the past 20 years, we decompose the realization of economic variables into the contributions of financial, monetary policy, and other shocks.
Keywords: 330